Corneal characteristics in Down syndrome patients with normal and keratoconic cornea - Hashemi, Hassan; Asgari, Soheila (Frontiers in Medicine, 2022)
Purpose To determine the reference range of corneal indices in Down syndrome patients with normal corneas (DS-N) and to compare it with the corneal indices in Down syndrome patients with keratoconic corneas (DS-KC). Methods A study was conducted using the data of 154 eyes of 154 DS-N and 25 eyes of 25 DS-KC patients. Eighteen indices related to thickness, anterior chamber, keratometry, elevation, and aberrations routinely used for KC diagnosis were extracted from the Pentacam. Results The mean age of the participants in DS-N and DS-KC groups was 16.73±4.70 and 16.56±4.22 years (p=0.852). In the DS-N group, 95% CI were 511.65‒520.31 for minimum corneal thickness, 2.97‒3.07 for anterior chamber depth (ACD), 46.83‒47.37 for maximum keratometry (Kmax), 46.13‒46.62 for zonal Kmax at 3mm, 0.35‒0.58 for inferior-superior asymmetry (I-S value), 1.56‒1.88 for Belin/Ambrósio display-total deviation, 8.65‒10.79 for best-fit-sphere posterior elevation at the thinnest point, and 0.18‒0.22 for corneal vertical coma. The age-related change in I-S value and corneal spherical aberration (SA) was significant (both P<0.05). There were significant inter-gender differences in 11 indices; the female DS patients had shallower, steeper, more elevated, and more aberrated corneas (all P<0.05). There were significant differences in all indices except for ACD (P=0.372) and corneal SA (P=0.169) between DS-N and DS-KC groups. Conclusion In DS patients aged 10-30 years, the reference ranges of corneal indices are different from the range reported for non-DS subjects and are close to values reported for mild KC non-DS cases. The normal values are different between DS male and female; hence, sex-specific ranges should be considered for diagnosis of corneal abnormality in DS patients.